The Influence of Human Resource Competency and Pharmacy Waiting Time on Patient Loyalty Mediated by Outpatient Satisfaction at RSHC - Wahyuningtyas, Heni; Tj, Hery Winoto; Saparso , Saparso (Syntax Literate, 2026)
Pharmaceutical services play a crucial role in shaping patient experiences and loyalty in healthcare institutions. This study examines the influence of human resource competency and pharmacy waiting time on patient loyalty mediated by outpatient satisfaction at RSHC, a private hospital established in 2021. The research addresses the declining trend in patient revisits, with old patient visits dropping from 762 in September 2024 to 346 in August 2025, despite stable total visit numbers. Using a quantitative approach, data were collected from 100 outpatient respondents who had visited the RSHC executive polyclinic at least twice, utilizing a structured questionnaire measured with a Likert scale. Data analysis employed partial least squares structural equation modeling (PLS-SEM) using SmartPLS version 4 software, including outer model testing (validity and reliability), inner model evaluation (R-square, F-square, Q-square, and model fit), and hypothesis testing. The results revealed that human resource competency and pharmacy waiting time do not directly affect patient loyalty but significantly influence it through patient satisfaction as a mediating variable. Specifically, HR competency (r=0.479, p=0.004) and pharmacy waiting time (r=0.428, p=0.009) positively affect patient satisfaction, which in turn strongly impacts patient loyalty (r=0.913, p=0.000). The indirect effects showed HR competency (r=0.438, p=0.004) and pharmacy waiting time (r=0.391, p=0.013) significantly influence loyalty through satisfaction. These findings emphasize that patient satisfaction serves as a critical bridge connecting service quality dimensions with patient loyalty, suggesting hospitals should focus on enhancing pharmacist competencies and service efficiency to create satisfying patient experiences and foster long-term loyalty.